Analisis Kinerja Inseminator IB pada ditinjau dari Kompensasi, Motivasi dan Disiplin kerja - Diah Iswana Rachmawati (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Performance is an output that is resulted by functions or indicators of work or profession at certain time (Wirawan, 2009). The objective of this research is to determine the influence of compensation (X1), motivation (X2) and discipline (X3) towards performance (Y) of inseminators of artificial insemination at Animal Health and Husbandry Department in Tulungagung District. This research is a causal comparative with quantitative approach that uses number (Likert Scale). It uses 50 respondents as population whom are inseminators of artificial insemination at Animal Health and Husbandry Department in Tulungagung District. The primary data is collected by using questionnaire. The data analysis method used in this research is quality test, classic assumption test and simple linier regression analysis. The research result indicates: (1) There is positive and significant influence of compensation towards performance of inseminators of artificial insemination at Animal Health and Husbandry Department, (2) There is positive and significant influence of motivation towards performance of inseminators of artificial insemination at Animal Health and Husbandry Department, (3) There is positive and significant influence of discipline towards performance of inseminators of artificial insemination at Animal Health and Husbandry Department. Data analysis result obtains dominating result of discipline, motivation and the less of compensation. It concludes that compensation which is given already fulfilling the need; otherwise, motivation and discipline need to be improved in order to gain maximum performance of inseminators of artificial insemination at Animal Health and Husbandry Department. The improvement of performance of inseminators of artificial insemination will influence directly towards increasing population of beef cattle and dairy cattle.